(untitled) (International Conference on Economics, Business, and Management Research (ICEBMR), 2024)
Economic growth is a key indicator in measuring the economic level of a country that is closely related to national development. The purpose of this study is to analyze the effect of local taxes, capital expenditure, expenditure on goods and services and domestic investment on economic growth in Sumatra. This study uses explanatory research and descriptive research methods, using panel data, consisting of 10 provinces in Sumatra from 2019 to 2021, sourced from the Central Statistics Agency (BPS), the Directorate General of Fiscal Balance (DJPK), and One Data Ministry of Trade. This study uses a panel data test, which consists of CEM, FEM and REM model tests. Based on the results of tests conducted by researchers, three of the four independent variables used in this study have a significant effect on economic growth in Sumatra. the variables in question are local taxes, and domestic investment has a positive and significant effect. The capital expenditure variable has a negative and significant effect. Meanwhile, the other independent variable, namely spending on goods and services, has a positive and insignificant effect on economic growth in Sumatra.